Comment: Some Remarks on Ethiopia’s New Cybercrime Legislation - Yilma, Kinfe Micheal (Mizan law review, 2017)
Ethiopia has been enacting various pieces of legislation, since recently, to regulate some aspects of the digital environment. The Cybercrime Proclamation of 2016 (Computer Crime Proclamation No.958/2016) is the most recent addition to the legal regime that criminalizes a range of cybercrimes. It has also introduced a number of novel evidentiary and procedural rules that will assist in the investigation and prosecution of cybercrimes. The law has, however, attracted criticisms from various corners mainly owing to some of its human rights unfriendly provisions. This piece provides brief comments on the cybercrime legislation and highlights some of the challenges that lie ahead in the course of implementing the law.